Pituitary Spindle Cell Oncocytoma: More than a Grade 1 Tumor? - Jonathan Hammond; Zacharie Gagne; Bojana Mitrovic; Stefano M. Priola (Neurology International)
Background/Objectives: Spindle cell oncocytomas (SCOs) of the pituitary gland are rare tumors often misdiagnosed for nonfunctioning pituitary macroadenomas. Although classified as grade 1, they are often challenging in terms of diagnosis and treatment. Pituitary SCOs harbor peculiar features such as hypervascularity and stronger adherence to surrounding structures, with increased risk of hemorrhage, partial resection, and significantly higher recurrence rate. Almost 100 cases have been reported so far. The role of surgery is still crucial for the decompression of the optic chiasm as well as for achieving diagnosis. However, given the higher tendency of recurrence, the role of postoperative radiotherapy has been investigated over the last few years. Case presentation: Here, we reported a case of a 48-year-old female with a pituitary SCO treated at our institution, in which we focused on diagnosis, treatment, and follow-up. Conclusions: This type of tumor presents a challenge related to its higher vascularity and strong adherence to the surrounding structures. Adjuvant radiotherapy is something that should be considered, especially when gross total resection is not achieved, and finally, SCOs require diligent follow-up to monitor for any signs of disease recurrence or progression.